Heparin and proteoglycans as anti-inflammatory drugs - Tyrrell, D. J.; Page, C. P. (Hämostaseologie, 1996)
Evidence continues to accumulate that the pleiotropic nature of heparin (beyond its anticoagulant potency) includes anti-inflammatory activities at a number of levels. It is clear that drugs exploiting these anti-inflammatory activities of heparin may offer exciting new therapeutic applications to the treatment of a wide range of inflammatory diseases.
Keywords: Heparin; proteoglycans; inflammation; neutrophils; growth factors